Quaternary pedostratigraphy of the Nevado de Toluca volcano - Elizabeth Solleiro-Rebolledo; José Luis Macías; Jorge Gama-Castro; Sergey Sedov; Leopold D. Sulerzhitsky (Revista Mexicana de Ciencias Geológicas)
Paleosol sequences of the Nevado de Toluca volcano (NTV) preserve a detailed record of late Quaternary environmental change. In fact, some studies have been used the NTV paleosols to interpret paleoenvironmental conditions, however some uncertainties still remain concerning their stratigraphic position and correlation. In this paper, we present the results of the NTV pedostratigraphy by using different paleosol units and based on present day tephrostratigraphy. We recognized eight Pleistocene paleosols, labeled PT0–PT7 which cover the 100,000–10,000 yr BP interval. These paleosols are located in four exposures: Arroyo La Ciervita, in the northern flank of the volcano, Zacango, in the northeast, and San Pedro Tlanisco and Barranca Cieneguilla, in the eastern part. The younger five paleosols correspond to different intergrades of Andosols (PT0–PT4) while the older sequence consists of three well developed Luvisols (PT5–PT7). All Andosols have humic horizons allowing radiocarbon dating. PT0 and PT1 were formed at the end of the Pleistocene and correlate with the oxygen isotope stage (OIS) 1 and to the middle-late OIS-2, respectively; the time for PT2 formation corresponds to the end of OIS- 3 and the beginning of OIS-2, PT3 to the OIS-3, and PT4 to the OIS-4. PT5–PT7 have not yet been dated, but we correlate them with the OIS-5a and 5b. A more strongly developed paleosol (PT1) was formed during the Last Glacial Maximum (18,000 yr BP) in comparison with other paleosol sequences where weakly developed paleosols were reported or even no soil formation was achieved in this period. We conclude that during late Pleistocene to Holocene, OIS 5 to 1, paleosol sequences of the Nevado de Toluca provide good environmental resolution, similar to or even higher than loess-paleosol sequences, although stratigraphic correlation with other paleoenvironmental records is more difficult because of the heterogeneity of volcanic sediments.